Educational Potential of Cities – Russian University Centers as a Factor of Increasing Their Competitiveness - T. F. Kreydenko; M. D. Petrovic; V. N. Kholina (Высшее образование в России)
The current stage of the country development is characterized by increasing the role of universities not only in the educational and public space of the country, but also in the socio-economic advancement of cities and regions. Universities forming the educational potential of the cities are flagships of their technological transformation, form the city brand, increase their sustainability, lifeabitity and competitiveness. The aim of the study is the typologization of cities – university centers of Russia, carried out with the help of a comprehensive index of educational potential developed by the authors. The statistical base for assessing the educational potential of cities was the data of the Monitoring of the effectiveness of the educational institutions of higher education in 2022, university rankings of the British company Quacquarelli Symonds (integral QS ranking and 5 integrated areas of study), RA-Expert (integrated and individual in 29 areas of study), the Three Missions of the University rating, and the University Reputation Ranking.The study was carried in 3 stages, each of them involved special methodological approaches. At the first stage, there was a review of existing theoretical and practical research on the subject, the integrated index of the educational potential of university centers was developed. At the second stage of the study on the bases of this index a typology of university centers of the Russian Federation was carried out. At the third stage, there was a comparation of the previous results with their positions in the Sustainable Urban Development Index and realization of creative potential. The implementation of educational potential of the most sustainable competitive university centers was separately analyzed in the context of the strategy of internationalization and export of education.National project “Science and Universities” aimed at formation of 100 universities as centers of scientific, technological and socio-economic development by 2030, as well as the program for the construction of 25 world-level modern campuses increase attention to cities as centers of localization of higher education, their educational potential, and, ultimately, their competitiveness.The scientific importance of the research is the development of methodological approaches to assessing the educational potential of cities – university centers and its testing on the example of 1208 universities located in 306 cities of 84 regions of Russia. As a result, a typology of Russian university centers was carried out according to the level of educational potential: 6 types of cities were identified, differing in the city-forming role of higher educational institutions, their role in brand formation and the competitiveness of the city.The typology makes it possible to assess the educational potential of university centers in Russia to form effective strategies for their development in the context of the realizing the national development goals of Russia.